The role of sensitization in musculoskeletal shoulder pain - Borstad,John (2015)
Introduction: Peripheral and central sensitization are neurophysiological processes that can prolong painful conditions. Painful shoulder conditions are often persistent, perhaps due to the presence of sensitization.Method:This manuscript summarizes six studies that have evaluated those with musculoskeletal shoulder pain for the presence of sensitization.Results:All six manuscripts report evidence of peripheral sensitization, while central sensitization was described in five of the studies. The chronicity of symptoms in subjects who were included in the studies is probably influencing this finding. The primary somatosensory test used to assess sensitization in these studies was Pressure Pain Threshold, a test for lowered nociceptive thresholds.Discussion:It appears that peripheral sensitization manifests consistently in those with musculoskeletal shoulder pathology, probably due to the inflammatory processes related to tissue injury. Central sensitization, while not universally present, was reported in a majority of the manuscripts. Because central sensitization is thought to be a key step on the pathway to chronic pain, evidence for its presence in those with shoulder pain is significant. Clinicians should expect the presence of sensitization with shoulder pathology and make appropriate choices about interventions so as not to exacerbate pain.